A brief history of paediatric urology in the UK. Issue 6 (14th December 2017) - Whitaker, Robert
Abstract : Robert Whitaker has lived through the exciting and challenging times covering the development and maturation of paediatric urology. In this article he provides his perspective on the development of the specialty and the key players who made it happen.